Development of megawatt radiofrequency ion source for the neutral beam injector on HL-2A tokamak. (15th February 2021) - Lei, G.J.; Yan, L.W.; Liu, D.P.; Zhang, X.M.; Zhao, M.; Geng, S.F.; Li, M.; Zhang, Y.X.; Bi, Z.H.; Bu, Y.N.; Xie, W.M.; Zou, G.Q.; et al.
Abstract: A radiofrequency (RF) ion source with a megawatt power extraction, thunder I, has been developed for the neutral beam injector (NBI) on HL-2A tokamak. A full solid-state RF generator with output power of 80 kW and frequency of 2 MHz was built by an RF combiner using 8 modules of solid-state RF generator with power of P RF = 10 kW. The line electric efficiency of whole RF generator reaches 92% and its voltage standing wave ratio (VSWR) is 1.01, thus no water-cooling system is supplied. A quartz vessel with the inner diameter of 250 mm is directly adopted for resisting atmospheric pressure, which can dramatically simplify source structure. Nowadays, the extracted beam parameters of RF hydrogen ion source are 32 kV/20 A/0.1 s on a test bed, while the design parameters are 50 kV/20 A/3 s. The beam density profile measured by the infrared imaging technique at 1.3 m downstream from the grounded grid obeys a Gaussian distribution, and the corresponding half width of 1/ e power decay at the matched condition is about 80 mm. Plasma homogeneity is over 90% at low RF power. The beam divergence angle meets the requirement of NBI system on HL-2A tokamak. The extractable current density increases almost linearly with the RF power. It reaches 2400 A m −2 at P RF = 32 kW. The ion density in front of plasma grid is about 1 × 10 18  m −3, corresponding to an ionized fraction of about 1% at the gas pressure of 0.5 Pa. Single hydrogen ion fraction reaches 79% at the beam current of 12.4 A. Some improvements have been considered for optimizing ion source performance on next experimental campaign. One smaller auxiliary RF discharge chamber equipped with a gas feed path, driven by 13.56 MHz/3.5 kW generator, is connected to main discharge chamber driven by 2 MHz/40 kW generator. By this dual-driven configuration, the innovative RF plasma source with high-pressure density gradient solves the initial ignition problem of powerful RF ion source even if the gas pressure below 0.1 Pa. In addition, the RF negative hydrogen ion source of 200 kV/20 A/3600 s is also developed at SWIP for the China fusion engineering test reactor.